The effects of metformin in the treatment of osteoarthritis: Current perspectives - Song, Yanhong; Wu, Ziyi; Zhao, Ping (Frontiers in Pharmacology, 2022)
Osteoarthritis is a chronic and irreversible disease of the locomotor system which is closely associated with advancing age. Pain and limited mobility frequently affect the quality of life in middle-aged and older adults. With a global population of more than 350 million, osteoarthritis is becoming a health killer alongside cancer and cardiovascular disease. It is challenging to find effective treatments to promote cartilage repair and slow down disease progression. Metformin is the first-line drug for patients with type 2 diabetes, and current perspectives suggest that it cannot only lower glucose but also has anti-inflammatory and anti-aging properties. Experimental studies applying metformin for the treatment of osteoarthritis have received much attention in recent years. In our review, we first presented the history of metformin and the current status of osteoarthritis, followed by a brief review of the mechanism that metformin acts, involving AMPK-dependent and non-dependent pathways. Moreover, we concluded that metformin may be beneficial in the treatment of osteoarthritis by inhibiting inflammation, modulating autophagy, antagonizing oxidative stress, and reducing pain levels. Finally, we analyzed the relevant evidence from animal and human studies. The potential of metformin for the treatment of osteoarthritis remains to be further explored.